Altitudinal shifts of the native and introduced flora of California in the context of 20th‐century warming. Issue 4 (20th January 2016) - Wolf, Adam; Zimmerman, Naupaka B.; Anderegg, William R. L.; Busby, Posy E.; Christensen, Jon
Abstract: Aim: The differential responses of plant species to climate change are of great interest and grave concern for scientists and conservationists. One underexploited resource for better understanding these changes are the records held by herbaria. Using these records to assess the responses of different groups of species across the entire flora of California, we sought to quantify the magnitude of species elevational shifts, to measure differences in shifts among functional groups and between native and introduced species, and to evaluate whether these shifts were related to the conservation of thermal niches. Location: California. Methods: To characterize these shifts in California, we used 681, 609 georeferenced herbarium records to estimate mean shifts in elevational and climatic space of 4426 plant taxa. We developed and employed a statistical method to robustly analyse the data represented in these records. Results: We found that 15% of all taxa in California have ranges that have shifted upward over the past century. There are significant differences between range shifts of taxa with different naturalization statuses: 12% of endemic taxa show significant upward range shifts, while a greater proportion (27%) of introduced taxa have shifted upward. We found significant differences between the proportion of significant range shifts across taxa with different seed sizes, but did not find evidence for differences in shift based on life‐form (annual versus perennial, herbaceous versus woody). Main conclusions: Our analyses suggest that introduced species have disproportionately expanded their ranges upward in elevation over the past century when compared with native species. While these shifts in introduced species may not be exclusively driven by climate, they highlight the importance of considering the interacting factors of climate‐driven range shifts and invasion to understand how floras are responding in the face of anthropogenic change.